Introducing the Record of Decision‐Making: A New Formative Assessment for Oral Reading. - Rodgers, Emily M.; D'Agostino, Jerome V. (Reading Teacher, 2026)
In this "Teaching and Learning in Practice" article, we introduce the record of decision‐making (RODM), a formative assessment of decoding while reading that measures the frequency of a student's use of backup strategies while reading aloud. We first explain backup strategies and then share validation and reliability evidence for the backup strategies that we include on the RODM. We also describe how to administer and interpret the results. At the end of the article, we provide a link to free, asynchronous training materials.